Observations and simulations of large-scale traveling ionospheric disturbances during the January 14-15, 2022 geomagnetic storm - Zhang, Kedeng; Wang, Hui (Frontiers in Astronomy and Space Sciences, 2023)
Using the total electron content (TEC) observations from GPS, and simulations from the Thermosphere Ionosphere Electrodynamic General Circulation Model (TIEGCM), this work investigates the largescale traveling ionospheric disturbances (LSTIDs) and the possible involved drivers during the geomagnetic storm on January 14-15, 2022. Based on the term analysis of O + continuity equation in TIEGCM, it is found that the traveling atmospheric disturbances in equatorward winds are responsible for the LSTIDs, with minor contributions from plasma drifts owing to the prompt penetration electric field. A strong interhemispheric asymmetry of the LSTIDs is observed, which might be attributed to both the equatorward wind disturbances and background plasma. The stronger wind (plasma) disturbances occurs in the winter hemisphere than that in the summer hemisphere. The maximum magnitude of LSTIDs in electron density disturbances occurs at ~250 and ~270 km in the northern and southern hemispheres, respectively, owing to both the thermospheric equatorward winds and background plasma. An interesting phenomenon that tail-like LSTIDs occur at the dip equator and low latitudes might be related to the eruption of the Tonga volcano, but it is not well reproduced in TIEGCM that deserves further exploration in a future study.